Heavy Equipment Education 2.0 Development as an Android-Based Learning Space - Hasan Maksum; Hannyka Febriano (IJECA (International Journal of Education and Curriculum Application), 2021)
The pandemic period of covid-19 is a difficult time for students and teachers, especially in the vocational high school students. One of the difficulties faced by students is learning online from home while many students do not have internet access. So developed an android application that can be accessed online and offline to help students in learning from home. The purpose of this research is to create a product in the form of android-based learning media that is valid, practical, and effective, so as to help the learning process during the Covid-19 pandemic. This application was then named Heavy equipment Education 2.0. This research is a development research that uses four-D method (define, design, development, disseminate) as the development method. From the research that has been done, it can be concluded that Heavy equipment Education 2.0 application is valid as a learning medium with a validity value of 0.94. Heavy equipment Education 2.0 application. practicality with a practicality score by the teacher of 91.5% while the practicality score by the student is 90%. As for its effectiveness value, Heavy equipment Education 2.0 application. able to improve student learning outcomes 97%.